Pemurnian Minyak Jelantah Menggunakan Adsorben Natural Dari Pelepah Sawit dengan Perbedaan Ukuran Mesh dan Massa - Fithry , Dwi Annisa; Haryanto, Bode; Affandi, Rizki; Hutabarat, Asrina; Febrisma, Anggun (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Indonesia is the second largest producer of palm oil in the world today after Malaysia. Since 2003, the amount of palm oil production in Indonesia has reached approximately 9.9 million tons per year. According to (BPS 2021), the area of oil palm land in North Sumatra reached 442 072.76 hectares. This research will purify used cooking oil using natural adsorbents by utilizing palm frond waste. Palm fronds are chopped into powder, then sifted with sizes of 50, 70 and 100 mesh after which they are weighed with weights of 1.5, 3 and 4.5 grams. Oil palm frond adsorbents with mass variations of 4.5 grams have the greatest adsorption power in reducing used cooking oil and the best adsorption kinetics based on the correlation coefficient is the pseudo second order equation.